Bismuth-cerium bimetal-based composite material as well as preparation method and application thereof

By combining CeO2 with Bi19Br3S27 to form a Bi19Br3S27/CeO2 heterojunction composite material, the existing photocatalyst CO2 has been solved, and efficient CO2 reduction and excellent cycle stability have been achieved.

CN119565643APending Publication Date: 2025-03-07JISHOU UNIVERSITY

Patent Information

Application Number
CN202411855484.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing photocatalysts have low photocatalytic reduction efficiency in CO2 and poor CO selectivity, making it difficult to effectively use solar energy for the production of hydrocarbon fuel.

Method used

By combining CeO2 with Bi19Br3S27, a Bi19Br3S27/CeO2 heterojunction composite material is formed, and its close contact heterointerface and S-type charge transfer pathway is used to promote the rapid transfer and separation of photogenerated carriers and broaden the absorption range of sunlight.

Benefits of technology

The CO2 photocatalytic reduction performance and CO selectivity are significantly improved, with high yield per unit time, strong selectivity, and excellent cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565643A_ABST
    Figure CN119565643A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of CO2 photocatalytic reduction, and particularly discloses a bismuth-cerium double-metal-based composite material and a preparation method and application thereof.The bismuth-cerium double-metal-based composite material is characterized in that CeO2 and Bi19Br3S27 are combined to obtain a Bi19Br3S27 / CeO2 heterojunction with a close contact heterogeneous interface and an S-type charge transfer pathway; compared with the prior art, the composite material provided by the invention can drive rapid transfer and separation of photon-generated carriers, widens the absorption range of sunlight, and has strong CO2 photocatalytic reduction performance and remarkable CO selectivity compared with the existing photocatalytic material. In addition, the preparation process flow is simple, the required raw materials can be obtained through commercially available purchase, large-scale industrial popularization and application are convenient to realize, and the preparation method has wide market prospects and remarkable social and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the synthesis of a photocatalytic material, in particular to a bismuth-cerium bimetallic composite material and a preparation method and application thereof, belonging to the technical field of photocatalytic material synthesis. Background Art

[0003] Photocatalytic technology uses sunlight as energy and semiconductor materials as catalysts to simulate plant photosynthesis to convert CO2 and H2O into high-value-added hydrocarbon fuels, which can not only reduce the content of CO2 in the atmosphere, but also alleviate the current energy shortage problem. Using hydrocarbon fuels as carriers to achieve the recycling of carbon in the atmosphere will help achieve the "dual carbon" goal.

[0004] Chinese patent document CN114054013A discloses a CeO2-TiO2 composite aerogel photocatalyst prepared by a sol-gel method combined with a supercritical drying process and high-temperature heat treatment. The heterojunction between CeO2 and TiO2 is used to improve the utilization efficiency of visible light. The CH4 production reaches about 0.7 to 1.4 μmol / (g·h), and the CO production reaches about 3.78 to 6.23 μmol / (g·h). A Chinese patent document discloses the preparation of an α-ferric oxide / titanium dioxide nanocomposite material and its application in the photocatalytic reduction of carbon dioxide. The preparation method comprises firstly preparing a sea urchin-shaped α-Fe2O3 by a hydrothermal method, and then preparing TiO2 nanosheets by solvent thermal method using hydrofluoric acid and tetrabutyl titanate. The α-Fe2O3 and TiO2 nanosheets are reacted at 150°C, and after the reaction, the α-Fe2O3 / TiO2 nanocomposite material is washed with deionized water and dried to obtain a α-Fe2O3 / TiO2 nanocomposite material having a maximum generation rate of CO and CH4 of 1.4 μmol / (g·h) and 8 μmol / (g·h), respectively. Chinese patent document CN115254115A discloses a Co / C-TiO2 composite material, the preparation process of which is as follows: S1, adding 2-methylimidazole and cobalt salt to an alcohol solvent to react for 5-24 hours, and adding a weak acid to mix; S2, mixing a titanium source with an alcohol solvent, and then mixing and reacting with the solution obtained in S1, and then standing and drying to obtain a gel; S3, calcining the gel under an inert atmosphere, and finally washing and drying to obtain a Co / C-TiO2 composite material; its maximum CH4 yield is about 1.8μmol / (g·h), and the maximum CO yield is 29.4μmol / (g·h).

[0005] Although there are many kinds of photocatalytic materials, in general, existing photocatalysts generally have shortcomings such as low CO2 photocatalytic reduction efficiency and poor CO selectivity. Summary of the invention

[0006] In view of the problems that the existing photocatalysts in the prior art generally have low CO2 photocatalytic reduction efficiency and poor CO selectivity, the present invention constructs a bismuth-cerium bimetallic composite material and its preparation method and use, by combining CeO2 with Bi 19 Br3S 27 Combined with the Bi with close contact heterointerface and S-type charge transfer pathway 19 Br3S 27 / CeO2 heterojunction composite materials, which can drive the rapid transfer and separation of photogenerated carriers, broaden the absorption range of sunlight, and thus make the composite materials have strong CO2 photocatalytic reduction performance and significant CO selectivity.

[0007] In order to achieve the above technical objectives, the technical solutions adopted by the present invention are as follows:

[0008] According to a first embodiment of the present invention, a bismuth-cerium bimetallic composite material is provided: the composite material comprises Bi 19 Br3S 27 And the load on Bi 19 Br3S 27 CeO2 on.

[0009] Preferably, in the composite material, the loading amount of CeO2 is Bi 19 Br3S 27 5 to 35 wt% of the mass, preferably 10 to 30 wt%, more preferably 15 to 25 wt%, more preferably 17 to 22%.

[0010] In this invention, a Bi-metallic nanostructured ... 19 Br3S 27 / CeO2 heterojunction composite materials are beneficial to promote charge transfer and separation. To this end, transient photocurrent (IT) and electrochemical impedance spectroscopy (EIS) tests were performed to verify the photoinduced charge transfer and separation behavior. The results show that compared with a single Bi 19 Br3S 27 (BBS) or CeO2, the Bi 19 Br3S 27 / CeO2 has a high photocurrent response (the highest when the CeO2 loading is between 15 and 25 wt%, for example, when the loading is 20%), indicating that its photoinduced carrier transfer capability has been greatly improved. 19 Br3S 27 / CeO2 catalyst has a smaller arc diameter (the smallest when the CeO2 loading is between 15 and 25 wt%, for example, when the loading is 20%). This is because Bi 19 Br3S27 A close contact heterojunction structure is formed between CeO2, which can drive the rapid transfer and separation of photogenerated carriers and broaden the absorption range of sunlight. 19 Br3S 27 It can serve as an effective channel to extract photoexcited charges from CeO2 and effectively suppress radiative recombination.

[0011] In the present invention, the photoelectrochemical test was conducted by an electrochemical workstation (CHI650E) and a standard three-electrode system. 0.1M Na2SO4 was used as the electrolyte solution for the photoelectrochemical measurement. The prepared catalyst was deposited on a fluorine-doped tin dioxide (ITO) conductive glass sheet to obtain a working electrode, while Ag / AgCl and Pt electrodes were used as reference electrodes and counter electrodes, respectively. Working electrode preparation method: 10 mg of the synthesized Bi 19 Br3S 27 / CeO2 photocatalytic material, 3mL ethanol and 30μL Nafion solution were added to the centrifuge tube, the mixture was ultrasonicated for 30min, the washed and dried ITO conductive glass sheet was placed in the centrifuge tube, and centrifuged at 7000rpm for 3min to make the sample evenly cover the ITO glass conductive surface. The photocurrent (IT) test used a 300W xenon lamp for several switching cycles of light irradiation, the stabilization time was 30s, and then the signal value was collected. The initial voltage of the electrochemical impedance spectroscopy (EIS) test was the measured open circuit voltage value, and a 5mV sinusoidal AC potential was used to collect signals in the frequency range of 0.01Hz to 100kHz. The Mott-Schottky curve test was set with the measured open circuit voltage as the center -(0.5~1)V as the starting potential, +(0.5~1)V as the termination potential, and the amplitude was 0.01V. The tests were conducted at frequencies of 1000Hz and 1500Hz, respectively.

[0012] In the present invention, in order to understand the reasons for the enhanced catalytic performance of the bismuth-cerium bimetallic matrix composite material of the present invention, the N2 adsorption-desorption isotherm was used to study the specific surface area and pore size distribution of the sample. 19 Br3S 27 The Brunauer-Emmett-Teller surface (S BET ) Area is about 3.7m 2 g -1 , while Bi 19 Br3S 27 S / CeO2 catalytic materials BET Area: approximately 32.4m 2 g -1 , S of CeO2 catalyst alone BET Area: approximately 117.2m2 g -1 It can be inferred that the introduction of CeO2 increases the 19 Br3S 27 S / CeO2 catalyst BET area, thereby increasing the active sites during the reaction process.

[0013] Furthermore, the present invention also uses ultraviolet-visible diffuse reflectance spectroscopy (UV-vis DRS) to test the optical properties of the bismuth-cerium bimetallic matrix composite material sample. The results show that the absorption edge of CeO2 is about 500nm. It is worth noting that Bi 19 Br3S 27 It has a wider absorption range and still has strong light absorption in the near-infrared region. Compared with CeO2 alone, Bi 19 Br3S 27 / CeO2 catalytic material has a red shift in absorption edge, indicating that Bi 19 Br3S 27 The light absorption capacity of the / CeO2 catalytic material is effectively improved. In order to understand the photoexcited charge transfer characteristics, the Bi 19 Br3S 27 The band structure of the / CeO2 heterojunction. The Mott-Schottky (MS) curve shows that Bi 19 Br3S 27 The flat band potentials of CeO2 and CeO2 are -0.9 and -0.46 V vs. NHE, respectively. Combined with the Eg value measured by UV-vis, the Bi 19 Br3S 27 The minimum conduction band edge (CBM) and maximum valence band edge (VBM) of CeO2 are -1.0 and 0.2 V (vs. NHE), respectively, and the minimum conduction band edge and maximum valence band edge of CeO2 are -0.56 and 2.05 V (vs. NHE), respectively, resulting in a staggered band structure. When they are in close contact with each other, due to the Bi 19 Br3S 27 The Fermi level of Bi is higher than that of CeO2. 19 Br3S 27 The free electrons at the Fermi level of will spontaneously migrate to the Fermi level of CeO2, inducing Bi 19 Br3S 27 and CeO2 upward and downward band bending, thus forming 19 Br3S 27 IEF pointing to CeO2. From the obtained band structure, it can be found that Bi 19 Br3S 27The conduction band (CB) potential of Bi is more negative than CO2 / CO (-0.52 V vs. NHE), indicating that they can reduce CO2 to CO. Under light conditions, 19 Br3S 27 The valence band electrons of CeO2 catalyst are excited and transferred to the conduction band. As a result, a type II or S-type transfer route may be formed, which further combines with Bi 19 Br3S 27 / CeO2 system, it is believed that the multi-electron reduction mechanism of the system does not conform to the type II transfer pathway; therefore, the Bi 19 Br3S 27 / CeO2 heterojunction should follow the S-scheme charge transfer mechanism, in which excited electrons are transferred from the CB of CeO2 to the Bi 19 Br3S 27 VB, and with the help of IEF and Bi 19 Br3S 27 The holes on VB combine, and Bi 19 Br3S 27 The electrons accumulated on the CB of CeO2 are transferred to the catalyst surface to reduce the adsorbed CO2 to CO; however, the holes are continuously accumulated on the VB of CeO2, and the holes are transferred to the catalyst surface to oxidize the adsorbed H2O to O2. This Bi 19 Br3S 27 / CeO2 heterojunction can promote the separation of photogenerated carriers and maintain the strong redox ability of the material.

[0014] In the present invention, in-situ XPS testing is further used to study the direction of electron transfer. 19 Br3S 27 The BE of Ce 3d and O1s signals in the CeO2 / CeO2 heterojunction shifted positively, indicating a decrease in electron density. The BE of Br 3d, Bi 4f and S2p signals in the heterojunction shifted negatively, which means that the electron density of Br, Bi and S increased under illumination. This opposite BE shift direction confirms that the photogenerated electrons in CeO2 are transferred to Bi under illumination. 19 Br3S 27 , following the S-type charge transfer route.

[0015] In the present invention, in order to further explore the carrier transport mechanism, femtosecond transient absorption (fs-TA) spectroscopy was used to analyze the dynamics of photogenerated charge carriers using 800 nm pump pulses. 19 Br3S 27In comparison, due to the S-type charge transfer mechanism, the complex exhibits a stronger negative absorption signal, among which a significant negative signal is observed at 600 nm, which is attributed to its ground state bleaching (GSB) signal, while a stronger negative signal is observed in the 700-900 nm range, indicating that Bi 19 Br3S 27 Due to the existence of S-type heterojunction in CeO2, the photogenerated electrons in the CB of CeO2 are transferred to Bi 19 Br3S 27 The VB and photogenerated holes recombine, resulting in the suppression of electron-hole recombination and signal reduction, which once again confirms the S-scheme carrier transport channel. 19 Br3S 27 A stronger positive signal was observed in the 900-950nm range in CeO2, which is due to the Bi 19 Br3S 27 / CeO2 excited state absorption (ESA). Therefore, the ESA signal originates from the electrons excited from the hybrid energy level to the Bi 19 Br3S 27 / CeO2 in CeO2 CB. The emergence of hybrid energy levels greatly expands the Bi 19 Br3S 27 / CeO2 composite material light absorption range.

[0016] In this invention, the decay dynamics of the fs-TA signal is analyzed in order to provide more insight into the carrier dynamics. 19 Br3S 27 The decay curve at 620 nm can be fitted by a bi-exponential model, indicating two different relaxation pathways for the photogenerated electrons. The one with the shorter lifetime (τ1 = 1.49 ps) corresponds to electron diffusion. However, the longer lifetime path, with τ2 = 25.88 ps, is attributed to the recombination of photogenerated electrons with trapped holes. 19 Br3S 27 The ESA decay curve of the / CeO2 composite material at 630nm can be fitted with a three-exponential model, indicating that there are three relaxation pathways. The fastest optical path (τ1 = 0.73ps) and the slowest optical path (τ3 = 453.23ps) are attributed to the diffusion of electrons and the recombination of electrons and holes, respectively, which is consistent with the Bi 19 Br3S 27 However, in Bi 19 Br3S 27 A unique process τ2 = 18.74 ps was found in / CeO2, which can be attributed to the hybridization of photogenerated electrons and photogenerated holes in Bi 19 Br3S 27This process illustrates the S-scheme electron transfer process and Bi 19 Br3S 27 -XPS results are consistent with the original Bi 19 Br3S 27 Compared with the electron-hole recombination in Bi 19 Br3S 27 The electron-hole recombination process in / CeO2 is significantly delayed, and the lifetime is extended from 25.88ps to 453.23ps. This is because the S-type heterojunction causes a large number of photoelectrons to recombine in Bi 19 Br3S 27 The photocurrent measurement and electrochemical impedance spectroscopy (EIS) were used to investigate the 19 Br3S 27 , CeO2 and Bi 19 Br3S 27 / CeO2 separation and transfer efficiency of photogenerated carriers. In EIS electrochemical impedance spectroscopy, Bi 19 Br3S 27 / CeO2 curve shows the smallest semicircle radius, which means the lowest carrier transfer impedance. Therefore, the S-type heterojunction is conducive to the transfer of electrons and holes to the photocatalyst surface, allowing them to participate in the photocatalytic reaction. Among them, the photocurrent density curve, Bi 19 Br3S 27 / CeO2 shows better 19 Br3S 27 The significantly higher photocurrent density of CeO2 and CeO2 indicates more efficient light harvesting and carrier utilization. Together, these results demonstrate the significant improvement in carrier transfer, separation, and utilization imparted by the S-scheme heterojunction.

[0017] According to a second embodiment of the present invention, a method for preparing a bismuth-cerium bimetallic composite material or a method for preparing a bismuth-cerium bimetallic composite material as described in the first embodiment is provided: the method comprises the following steps:

[0018] 1) The sulfur source, bismuth source and bromine source are subjected to liquid phase thermal synthesis reaction, and solid-liquid separation is performed to obtain Bi 19 Br3S 27 .

[0019] 2) Change Bi 19 Br3S 27 Add to the cerium source solution and mix evenly, then add alkali to the mixed system for mixing reaction. 19 Br3S 27 CeO2 loaded Bi 19 Br3S 27, solid-liquid separation to obtain bismuth-cerium bimetallic matrix composite material.

[0020] Preferably, the sulfur source is elemental sulfur and / or an organic sulfur compound. Preferably, the organic sulfur compound includes but is not limited to one or more of thiols, thioethers, thiophenols, disulfides, polysulfides, and thiocarbonyl compounds. More preferably, the organic sulfur compound is one or more of thiourea, thioacetamide, and thioacetone.

[0021] Preferably, the bismuth source is one or more of bismuth nitrate, bismuth sulfate, bismuth chloride, bismuth bromide, and bismuth sulfide, preferably one or more of bismuth nitrate, bismuth bromide, and bismuth sulfide.

[0022] Preferably, the bromine source is one or more of liquid bromine, bromine salts, and brominated hydrocarbons, preferably one or more of hexadecyl ammonium bromide, sodium bromide, potassium bromide, bismuth bromide, and ethylene dibromide.

[0023] Preferably, the cerium source is one or more of cerium (III) nitrate, cerium (IV) nitrate, cerium (III) sulfate, cerium (IV) sulfate, cerium (III) chloride, and cerium (IV) chloride, preferably cerium (III) nitrate and / or cerium (IV) sulfate.

[0024] As a preferred method, the cerium source and Bi 19 Br3S 27 The addition mass ratio is 5 to 35:100, preferably 10 to 30:100, and more preferably 15 to 25:100.

[0025] Preferably, the base is aqueous ammonia. Preferably, the amount of aqueous ammonia added is such that the pH of the reaction system is 8 to 11.5, preferably 9 to 11, and more preferably 9.5 to 10.5.

[0026] It should be noted that, in the present invention, when each raw material is limited to a salt, their hydrates should be included. For example, bismuth nitrate includes both anhydrous bismuth nitrate and bismuth nitrate hydrate (such as bismuth nitrate pentahydrate), and cerium (III) nitrate includes both anhydrous cerium (III) nitrate and cerium (III) nitrate hydrate (such as cerium (III) nitrate hexahydrate).

[0027] Preferably, step 1) is specifically as follows: first, a sulfur source, a bismuth source, and a bromine source (the amounts of the three can be reasonably adjusted according to the stoichiometric ratio of each element in the target product) are respectively made into solutions and then mixed or dissolved together to obtain a mixed solution, and then the mixed solution is placed in a sealed reactor and reacted at 120 to 160° C. (preferably 130 to 150° C.) for 1 to 24 hours (preferably 6 to 18 hours) to obtain a crude product, and the crude product is washed with water and ethanol (for example, washed to neutrality), and finally dried (for example, vacuum dried at 60 to 80° C. for 1 to 12 hours) to obtain Bi 19 Br3S 27 .

[0028] Preferably, step 2) is as follows: a cerium source is made into a solution (which may be heated or not, for example, heated to 40-60° C.) and then Bi is added thereto. 19 Br3S 27 , after mixing evenly, add alkali (such as ammonia water) and stir the reaction at 40-60°C (preferably 45-55°C) for 5-36h (preferably 8-30h) to obtain a crude product, then wash the crude product with water and ethanol (for example, wash to neutrality), and finally dry it (for example, dry it at 60-80°C for 1-12h) to obtain a bismuth-cerium bimetallic matrix composite material.

[0029] In step 1) and step 2), it should be noted that the choice of solvent can be selected according to the different sulfur sources, bismuth sources, bromine sources, cerium sources, etc., and is generally preferably the same solvent. The solvent can be water or an organic solvent. The organic solvent includes but is not limited to alcohols, acids, ethers, ketones, aromatics and their hydrocarbons or substituted hydrocarbon compounds.

[0030] In the present invention, the bismuth-cerium bimetallic matrix composite material (i.e., Bi 19 Br3S 27 / CeO2) was successfully synthesized by homogeneous precipitation method. XRD was used to study the phase structure of the synthesized composite material (i.e. catalyst). Figure 3 It can be seen that the prepared single Bi 19 Br3S 27 The characteristic diffraction peaks at 23.65°, 28.29°, and 41.71° correspond to Bi 19 Br3S 27 The characteristic diffraction peaks of the prepared single CeO2 at 28.05°, 33.01°, 47.21°, and 56.38° correspond to the (111)(200)(220)(311) crystal planes of CeO2, respectively. Both pure catalyst materials show a high level of consistency with the corresponding standard PDF cards. In addition, from Bi 19 Br3S27 / CeO2 composites, it can be seen that with the addition of CeO2, Bi 19 Br3S 27 The characteristic peak of diffraction intensity gradually weakened, and no other impurity diffraction peaks appeared, indicating that Bi 19 Br3S 27 / CeO2 heterojunction was successfully formed. Unless otherwise specified, the following discussion is all about the prepared Bi 19 Br3S 27 / CeO2 sample, where the CeO2 loading is 20wt%, marked as Bi 19 Br3S 27 / CeO2-20. The morphology, size and distribution characteristics of the sample were studied by SEM, so that the surface morphology and structural synthesis of the catalyst can be visualized. 19 Br3S 27 The SEM image shows that Bi 19 Br3S 27 It is a nanoscale sea urchin structure composed of uniform and densely arranged rod-like structures. 19 Br3S 27 It can be clearly seen in the SEM image of / CeO2-20 that CeO2 nanoparticles are deposited on Bi 19 Br3S 27 The surface of the sea urchin structure and the wrapping of the sea urchin structure into a more rounded spherical structure indicate that Bi 19 Br3S 27 / CeO2-20 was successfully synthesized. Further magnification of the TEM image showed that there were multiple groups of lattice fringes in the composite material, and the corresponding interlayer spacings were 0.35nm and 0.30nm, respectively, corresponding to Bi 19 Br3S 27 The (111) crystal plane and CeO2 (111) crystal plane of the composite catalyst reflect the polycrystalline characteristics. In addition, the element distribution diagram also found that Bi and S content is high, while Br, Ce and O content is low. The above experimental results show that Bi-containing 19 Br3S 27 Heterojunction composite materials of components and CeO2 components.

[0031] According to a third embodiment of the present invention, there is provided a use of a bismuth-cerium bimetallic composite material, or the use of the bismuth-cerium bimetallic composite material as described in the first embodiment, or the use of the bismuth-cerium bimetallic composite material obtained by the method described in the second embodiment: the bismuth-cerium bimetallic composite material is used as a photocatalytic material, preferably the bismuth-cerium bimetallic composite material is used for photocatalytic CO2 reduction.

[0032] In the present invention, a bismuth-cerium bimetallic composite material (Bi 19 Br3S 27 / CeO2) photocatalytic CO2 reduction reaction was carried out in a closed circulation system under simulated solar spectrum. The light source used was a 300W xenon lamp (MC-PF300, Beijing Magnesium Technology Co., Ltd.). The volume of the entire reaction system was about 455mL. Before irradiation, 6mg of the catalyst was uniformly dispersed on a circular quartz plate with a diameter of 3.2cm and a specification of G2 by ultrasound. The quartz plate was placed on a heater to dry, and the distance between the dried quartz plate and the light source was maintained at 9.4cm. Subsequently, 6mL of deionized water was injected into the reactor, and the entire glass system was vacuumed for 15min, and then CO2 (99.999%) gas was injected into the system to keep the entire system at normal pressure. The prepared photocatalyst was stabilized in a CO2 / H2O atmosphere for 30min to reach adsorption-desorption equilibrium. At a given time interval, a certain amount of gas was extracted, and the product was quantitatively analyzed by a gas chromatograph (GC 9790, Zhejiang Fuli Analytical Instrument Co., Ltd.). Bi was also carried out under the same conditions. 19 Br3S 27 / CeO2 cyclic stability experiment.

[0033] In the present invention, Bi is evaluated under simulated sunlight. 19 Br3S 27 / CeO2 catalysts for photocatalytic CO2 reduction. It is noteworthy that Bi 19 Br3S 27 / CeO2 catalytic system uses only water as a sacrificial agent for photocatalytic CO2 reduction. 19 Br3S 27 The catalyst has no obvious photocatalytic CH4 reduction activity. 19 Br3S 27 (BBS) only produced 0.54 μmol g -1 h -1 CH4, and a small amount of CO (about 5.53 μmol g -1 h -1 The single CeO2 sample also showed a lower CO yield (about 4.25 μmol g -1 h -1 ). 19 Br3S 27 After loading CeO2, the photocatalytic CO2 reduction performance was greatly enhanced, and the maximum CO yield could reach 65.09 μmol g -1 h -1 , than Bi alone 19 Br3S27 11.77 times higher than that of CeO2 alone and 15.32 times higher than that of CeO2 alone. 19 Br3S 27 The photocatalytic performance of the composite catalysts was significantly stronger than that of the two pure photocatalysts, highlighting their significant improvement in CO production rate. In addition, it should be noted that the appropriate loading of CeO2 plays a key role in improving the photocatalytic activity. With the increase of CeO2 content, the CO production of the composite catalysts first increased and then decreased. For example, when the CeO2 content was 20wt% (based on the mass of the carrier), the CO production of the Bi 19 Br3S 27 / CeO2 catalyst has good photocatalytic CO2 reduction activity. The results show that an appropriate amount of CeO2 can improve the separation ability of photoexcited electron-hole carriers in the composite material, but excessive CeO2 loading will reduce the active centers of the photoexcited reaction, resulting in a decrease in catalytic performance. This confirms that the generated carbon products originate from the introduced CO2 gas.

[0034] Compared with the prior art, the beneficial technical effects of the present invention are as follows:

[0035] 1: The bismuth-cerium bimetallic matrix composite material (Bi 19 Br3S 27 / CeO2) has excellent photocatalytic performance compared to existing photocatalytic materials, especially the catalytic reduction of CO2 to produce CO has a significant effect, high yield per unit time, strong selectivity, and excellent cycle stability.

[0036] 2: Preparation of Bi-Ce Bimetallic Composite Material (Bi 19 Br3S 27 The process of producing CeO2 is simple, and the required raw materials can be purchased from the market, which is convenient for large-scale industrial promotion and application, and has broad market prospects and significant social and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the SEM image of the BC-20 composite material prepared in Example 6 of the present invention.

[0038] Figure 2 This is a TEM image of the BC-20 composite material prepared in Example 6 of the present invention.

[0039] Figure 3 This is the XRD pattern of the BC-20 composite material prepared in Example 6 of the present invention.

[0040] Figure 4 Bi prepared in Example 12 of the present invention 19 Br3S 27 / CeO2-20 composite material XRD pattern.

[0041] Figure 5 This is the full XPS spectrum of the BC-20 composite material prepared in Example 6 of the present invention.

[0042] Figure 6 This is a photocurrent comparison diagram of the BC-20 composite material prepared in Example 6 of the present invention, BBS and CeO2.

[0043] Figure 7 This is a comparison chart of nitrogen adsorption-desorption curves of the BC-20 composite material prepared in Example 6 of the present invention, BBS and CeO2.

[0044] Figure 8 This is the SEM image of the BBS prepared in Preparation Example 1 of the present invention. DETAILED DESCRIPTION

[0045] The technical solution of the present invention is illustrated below by way of example, and the scope of protection requested by the present invention includes but is not limited to the following embodiments.

[0046] Preparation Example 1

[0047] First, 0.40 parts of thiourea, 0.20 parts of hexadecyltrimethylammonium bromide, and 0.19 parts of Bi(NO3)3·5H2O were dissolved in 20 parts of ethylene glycol and stirred for 0.5 hours to obtain a mixed solution; then the mixed solution was heat-treated at 130°C for 12 hours in a sealed polytetrafluoroethylene-lined reactor; then the obtained precipitate was washed with water and ethanol until neutral, and finally vacuum-dried at 60°C for 12 hours to obtain Bi 19 Br3S 27 (BBS for short).

[0048] Preparation Example 2

[0049] Preparation Example 1 was repeated except that thiourea was replaced by an equal molar amount of thioacetamide.

[0050] Preparation Example 3

[0051] Preparation Example 1 was repeated except that Bi(NO3)3 was replaced by an equal molar amount of BiCl3.

[0052] Preparation Example 4

[0053] Preparation Example 1 was repeated except that hexadecyltrimethylammonium bromide was replaced by an equimolar amount of sodium bromide.

[0054] Example 1

[0055] 0.055 parts of Ce(NO3)3·6H2O were dissolved in 20 parts of ethylene glycol solution with a volume fraction of 80%. During the dissolution process, the solution was heated to 50°C and stirred continuously until a uniform solution was obtained. Then 1.0 parts of Bi prepared in Preparation Example 1 was added. 19 Br3S 27 The powder was added to the above solution and ultrasonically dispersed for 10 minutes to obtain a mixed system; then an aqueous ammonia solution with a concentration of 3.0 mol / L was slowly added to the above mixed system to adjust the pH of the reaction system to 10, and the resulting suspension was stirred at 50°C for 24 hours, and then the system after the reaction was cooled to room temperature and filtered, and the solid product was washed with deionized water and ethanol until it was neutral; finally, the solid product was dried at 60°C for 12 hours to obtain the target product, which was marked as Bi 19 Br3S 27 / CeO2-2 (BC-2 for short).

[0056] Example 2

[0057] 0.126 parts of Ce(NO3)3·6H2O were dissolved in 20 parts of ethylene glycol solution with a volume fraction of 80%. During the dissolution process, the solution was heated to 50°C and stirred continuously until a uniform solution was obtained. Then 1.0 parts of Bi prepared in Preparation Example 1 was added. 19 Br3S 27 The powder was added to the above solution and ultrasonically dispersed for 10 minutes to obtain a mixed system; then an aqueous ammonia solution with a concentration of 3.0 mol / L was slowly added to the above mixed system to adjust the pH of the reaction system to 10, and the resulting suspension was stirred at 50°C for 24 hours, and then the system after the reaction was cooled to room temperature and filtered, and the solid product was washed with deionized water and ethanol until it was neutral; finally, the solid product was dried at 60°C for 12 hours to obtain the target product, which was marked as Bi 19 Br3S 27 / CeO2-5 (BC-5 for short).

[0058] Example 3

[0059] 0.252 parts of Ce(NO3)3·6H2O were dissolved in 20 parts of ethylene glycol solution with a volume fraction of 80%. During the dissolution process, the solution was heated to 50°C and stirred continuously until a uniform solution was obtained. Then 1.0 part of Bi prepared in Preparation Example 1 was added. 19 Br3S 27The powder was added to the above solution and ultrasonically dispersed for 10 minutes to obtain a mixed system; then an ammonia solution with a concentration of 3.0 mol / L was slowly added to the above mixed system to adjust the pH of the reaction system to 10, and the resulting suspension was stirred at 55°C for 24 hours, and then the system after the reaction was cooled to room temperature and filtered, and the solid product was washed with deionized water and ethanol until it was neutral; finally, the solid product was dried at 60°C for 12 hours to obtain the target product, which was marked as Bi 19 Br3S 27 / CeO2-10 (BC-10 for short).

[0060] Example 4

[0061] 0.379 parts of Ce(NO3)3·6H2O were dissolved in 20 parts of ethylene glycol solution with a volume fraction of 80%. During the dissolution process, the solution was heated to 50°C and stirred continuously until a uniform solution was obtained. Then 1.0 part of Bi prepared in Preparation Example 1 was added. 19 Br3S 27 The powder was added to the above solution and ultrasonically dispersed for 10 minutes to obtain a mixed system; then an ammonia solution with a concentration of 3.0 mol / L was slowly added to the above mixed system to adjust the pH of the reaction system to 10, and the resulting suspension was stirred at 55°C for 24 hours, and then the system after the reaction was cooled to room temperature and filtered, and the solid product was washed with deionized water and ethanol until it was neutral; finally, the solid product was dried at 60°C for 12 hours to obtain the target product, which was marked as Bi 19 Br3S 27 / CeO2-15 (BC-15 for short).

[0062] Example 5

[0063] 0.429 parts of Ce(NO3)3·6H2O were dissolved in 20 parts of ethylene glycol solution with a volume fraction of 80%. During the dissolution process, the solution was heated to 50°C and stirred continuously until a uniform solution was obtained. Then 1.0 part of Bi prepared in Preparation Example 1 was added. 19 Br3S 27 The powder was added to the above solution and ultrasonically dispersed for 10 minutes to obtain a mixed system; then an ammonia solution with a concentration of 3.0 mol / L was slowly added to the above mixed system to adjust the pH of the reaction system to 10, and the resulting suspension was stirred at 55°C for 24 hours, and then the system after the reaction was cooled to room temperature and filtered, and the solid product was washed with deionized water and ethanol until it was neutral; finally, the solid product was dried at 60°C for 12 hours to obtain the target product, which was marked as Bi 19 Br3S 27 / CeO2-17 (BC-17 for short).

[0064] Example 6

[0065] 0.505 parts of Ce(NO3)3·6H2O were dissolved in 20 parts of ethylene glycol solution with a volume fraction of 80%. During the dissolution process, the solution was heated to 50°C and stirred continuously until a uniform solution was obtained. Then 1.0 part of Bi prepared in Preparation Example 1 was added. 19 Br3S 27 The powder was added to the above solution and ultrasonically dispersed for 10 minutes to obtain a mixed system; then an ammonia solution with a concentration of 3.0 mol / L was slowly added to the above mixed system to adjust the pH of the reaction system to 10, and the resulting suspension was stirred at 55°C for 24 hours, and then the system after the reaction was cooled to room temperature and filtered, and the solid product was washed with deionized water and ethanol until it was neutral; finally, the solid product was dried at 60°C for 12 hours to obtain the target product, which was marked as Bi 19 Br3S 27 / CeO2-20 (BC-20 for short).

[0066] Example 7

[0067] 0.555 parts of Ce(NO3)3·6H2O were dissolved in 20 parts of ethylene glycol solution with a volume fraction of 80%. During the dissolution process, the solution was heated to 50°C and stirred continuously until a uniform solution was obtained. Then 1.0 part of Bi prepared in Preparation Example 1 was added. 19 Br3S 27 The powder was added to the above solution and ultrasonically dispersed for 10 minutes to obtain a mixed system; then an ammonia solution with a concentration of 3.0 mol / L was slowly added to the above mixed system to adjust the pH of the reaction system to 10, and the resulting suspension was stirred at 55°C for 24 hours, and then the system after the reaction was cooled to room temperature and filtered, and the solid product was washed with deionized water and ethanol until it was neutral; finally, the solid product was dried at 60°C for 12 hours to obtain the target product, which was marked as Bi 19 Br3S 27 / CeO2-22 (BC-22 for short).

[0068] Example 8

[0069] 0.631 parts of Ce(NO3)3·6H2O were dissolved in 20 parts of ethylene glycol solution with a volume fraction of 80%. During the dissolution process, the solution was heated to 50°C and stirred continuously until a uniform solution was obtained. Then 1.0 part of Bi prepared in Preparation Example 1 was added. 19 Br3S 27The powder was added to the above solution and ultrasonically dispersed for 10 minutes to obtain a mixed system; then an ammonia solution with a concentration of 3.0 mol / L was slowly added to the above mixed system to adjust the pH of the reaction system to 10, and the resulting suspension was stirred at 55°C for 28 hours, and then the system after the reaction was cooled to room temperature and filtered, and the solid product was washed with deionized water and ethanol until it was neutral; finally, the solid product was dried at 60°C for 12 hours to obtain the target product, which was marked as Bi 19 Br3S 27 / CeO2-25 (BC-25 for short).

[0070] Example 9

[0071] 0.757 parts of Ce(NO3)3·6H2O were dissolved in 20 parts of ethylene glycol solution with a volume fraction of 80%. During the dissolution process, the solution was heated to 50°C and stirred continuously until a uniform solution was obtained. Then 1.0 parts of Bi prepared in Preparation Example 1 was added. 19 Br3S 27 The powder was added to the above solution and ultrasonically dispersed for 10 minutes to obtain a mixed system; then an ammonia solution with a concentration of 3.0 mol / L was slowly added to the above mixed system to adjust the pH of the reaction system to 10, and the resulting suspension was stirred at 55°C for 24 hours, and then the system after the reaction was cooled to room temperature and filtered, and the solid product was washed with deionized water and ethanol until it was neutral; finally, the solid product was dried at 60°C for 12 hours to obtain the target product, which was marked as Bi 19 Br3S 27 / CeO2-30 (BC-30 for short).

[0072] Example 10

[0073] 0.883 parts of Ce(NO3)3·6H2O were dissolved in 20 parts of ethylene glycol solution with a volume fraction of 80%. During the dissolution process, the solution was heated to 50°C and stirred continuously until a uniform solution was obtained. Then 1.0 part of Bi prepared in Preparation Example 1 was added. 19 Br3S 27 The powder was added to the above solution and ultrasonically dispersed for 10 minutes to obtain a mixed system; then an ammonia solution with a concentration of 3.0 mol / L was slowly added to the above mixed system to adjust the pH of the reaction system to 10, and the resulting suspension was stirred at 55°C for 24 hours, and then the system after the reaction was cooled to room temperature and filtered, and the solid product was washed with deionized water and ethanol until it was neutral; finally, the solid product was dried at 60°C for 12 hours to obtain the target product, which was marked as Bi 19 Br3S 27 / CeO2-35 (BC-35 for short).

[0074] Embodiment 11

[0075] 1.010 parts of Ce(NO3)3·6H2O were dissolved in 20 parts of ethylene glycol solution with a volume fraction of 80%. During the dissolution process, the solution was heated to 50°C and stirred continuously until a uniform solution was obtained. Then 1.0 part of Bi prepared in Preparation Example 1 was added. 19 Br3S 27 The powder was added to the above solution and ultrasonically dispersed for 10 minutes to obtain a mixed system; then an ammonia solution with a concentration of 3.0 mol / L was slowly added to the above mixed system to adjust the pH of the reaction system to 10, and the resulting suspension was stirred at 55°C for 24 hours, and then the system after the reaction was cooled to room temperature and filtered, and the solid product was washed with deionized water and ethanol until it was neutral; finally, the solid product was dried at 60°C for 12 hours to obtain the target product, which was marked as Bi 19 Br3S 27 / CeO2-40 (BC-40 for short).

[0076] Example 12

[0077] 0.387 parts of Ce(SO4)2 were dissolved in 20 parts of ethylene glycol solution with a volume fraction of 80%. During the dissolution process, the solution was heated to 50°C and stirred continuously until a uniform solution was obtained. Then 1.0 part of Bi prepared in Preparation Example 1 was added. 19 Br3S 27 The powder was added to the above solution and ultrasonically dispersed for 10 minutes to obtain a mixed system; then an ammonia solution with a concentration of 3.0 mol / L was slowly added to the above mixed system to adjust the pH of the reaction system to 10, and the resulting suspension was stirred at 55°C for 24 hours, and then the system after the reaction was cooled to room temperature and filtered, and the solid product was washed with deionized water and ethanol until it was neutral; finally, the solid product was dried at 60°C for 12 hours to obtain the target product, which was marked as Bi 19 Br3S 27 / CeO2-20.

[0078] Comparative Example 1

[0079] Dissolve 0.521 parts of CuSO4·5H2O in 10 parts of deionized water, stir for 30 minutes until completely dissolved, then add 1.0 parts of Bi prepared in Preparation Example 1 19 Br3S 27 The powder was stirred for 6 hours, and then 20 parts of 0.5M NaOH solution was added to produce a blue precipitate. 25 parts of 0.1M ascorbic acid were added dropwise under stirring, and stirred for 30 minutes. The solid product was washed with deionized water and ethanol until it was neutral. Finally, the solid product was dried at 60°C for 12 hours to obtain the target product, which was labeled as Bi19 Br3S 27 / CuO2-15 (BCu-15 for short).

[0080] Comparative Example 2

[0081] Dissolve 0.694 parts of CuSO4·5H2O in 10 parts of deionized water, stir for 30 minutes until completely dissolved, then add 1.0 parts of Bi prepared in Preparation Example 1 19 Br3S 27 The powder was stirred for 6 hours, and then 20 parts of 0.5M NaOH solution was added to produce a blue precipitate. 25 parts of 0.1M ascorbic acid were added dropwise under stirring, and stirred for 30 minutes. The solid product was washed with deionized water and ethanol until it was neutral. Finally, the solid product was dried at 60°C for 12 hours to obtain the target product, which was labeled as Bi 19 Br3S 27 / CuO2-20 (BCu-20 for short).

[0082] Comparative Example 3

[0083] Dissolve 0.868 parts of CuSO4·5H2O in 10 parts of deionized water, stir for 30 minutes until completely dissolved, then add 1.0 parts of Bi prepared in Preparation Example 1. 19 Br3S 27 The powder was stirred for 6 hours, and then 20 parts of 0.5M NaOH solution was added to produce a blue precipitate. 25 parts of 0.1M ascorbic acid were added dropwise under stirring, and stirred for 30 minutes. The solid product was washed with deionized water and ethanol until it was neutral. Finally, the solid product was dried at 60°C for 12 hours to obtain the target product, which was labeled as Bi 19 Br3S 27 / CuO2-25 (BCu-25 for short).

[0084] Comparative Example 4

[0085] 0.200 parts of In2O3 were dissolved in 20 parts of ethylene glycol solution with a volume fraction of 80%. During the dissolution process, the solution was heated to 50°C and stirred continuously until a uniform solution was obtained. Then 1.0 parts of Bi 19 Br3S 27 The powder was added to the above solution and ultrasonically dispersed for 10 minutes to obtain a mixed system. The resulting suspension was then stirred and reacted at 55°C for 24 hours. The system after the reaction was cooled to room temperature and filtered, and the solid product was washed with deionized water and ethanol until it was neutral. Finally, the solid product was dried at 60°C for 12 hours to obtain the product, which was labeled as Bi. 19 Br3S 27 / In2O3-20 (abbreviated as BIn-20).

[0086] Comparative Example 5

[0087] 0.280 parts of Ni(NO3)2·6H2O, 0.120 parts of Al(NO3)3·9H2O, 0.094 parts of NH4F and 0.384 parts of urea were added to 80 parts of deionized water and stirred for 0.5 hours. The mixed solution was reacted in a sealed reactor at 120°C for 24 hours. After the reaction was completed, the generated precipitate was repeatedly washed with distilled water and ethanol until pH = 7, and finally vacuum dried at 60°C for 12 hours to obtain NiAl-LDH.

[0088] 0.505 parts of Ce(NO3)3·6H2O were dissolved in 20 parts of ethylene glycol solution with a volume fraction of 80%. During the dissolution process, the solution was heated to 50°C and stirred continuously until a uniform solution was obtained; then 1.0 parts of NiAl-LDH powder was added to the above solution, and ultrasonic dispersion was performed for 10 minutes to obtain a mixed system; then an ammonia solution with a concentration of 3.0 mol / L was slowly added to the above mixed system to adjust the pH of the reaction system to 10, and the obtained suspension was stirred at 55°C for 24 hours, and then the reacted system was cooled to room temperature and filtered, and the solid product was washed with deionized water and ethanol until it was neutral; finally, the solid product was dried at 60°C for 12 hours to obtain the target product, which was marked as NiAl-LDH / CeO2 (abbreviated as NC-20).

[0089] Photocatalytic reduction performance test

[0090] The photocatalytic CO2 reduction reaction was carried out in a closed circulation system under a simulated solar spectrum. The light source used was a 300W xenon lamp (MC-PF300, Beijing Magnesium Technology Co., Ltd.). The volume of the entire reaction system was about 455 mL. Before irradiation, 6 mg of catalyst (including different Bi prepared in Examples 1-11) was added to the reaction mixture. 19 Br3S 27 / CeO2 composite materials, Bi prepared in Comparative Examples 1-5 19 Br3S 27 / CuO2-15、Bi 19 Br3S 27 / CuO2-20、Bi 19 Br3S 27 / CuO2-25、Bi 19 Br3S 27 / In2O3-20, NiAl-LDH / CeO2 and Bi alone 19 Br3S 27and CeO2, etc., each catalytic material was tested separately during the test) was uniformly dispersed on a circular quartz plate with a diameter of 3.2 cm and a specification of G2 by ultrasound, and the quartz plate was placed on a heater to dry, and the distance between the dried quartz plate and the light source was maintained at 9.4 cm. Subsequently, 5 mL of deionized water was injected into the reactor, and the entire system was vacuumed for 10 minutes, and then CO2 (99.999%) gas was injected into the system to keep the entire system at normal pressure. The prepared photocatalyst was stabilized in a CO2 / H2O atmosphere for 30 minutes to achieve adsorption-desorption equilibrium. At a given time interval, a certain amount of gas was extracted, and the product was quantitatively analyzed by a gas chromatograph (GC 9790, Zhejiang Fuli Analytical Instrument Co., Ltd.). The test results are shown in the following table:

[0091]

[0092] The same test conditions as the above-mentioned photocatalytic reduction performance test were used to test the different Bi 19 Br3S 27 The cyclic stability test of photocatalytic CO2 reduction was carried out on the / CeO2 composite materials separately. The test results are shown in the following table:

[0093]

[0094] It can be seen from the test results in the above two tables that the bismuth-cerium bimetallic composite material prepared by the present invention is better than that of the single Bi 19 Br3S 27 For CeO2, it has excellent photocatalytic reduction performance for carbon dioxide and high selectivity for CO, and also has good cycle stability.

[0095] In the present invention, the reagents and equipment used in each preparation example, each embodiment and each comparative example are purchased from the market, for example: Ce(NO3)3·6H2O, Ce(SO4)2 and Bi(NO3)3·5H2O are all purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., hexadecyltrimethylammonium bromide is purchased from Shanghai McLean Biochemical Technology Co., Ltd., thiourea is purchased from Tianjin Yongda Chemical Reagent Co., Ltd., ethylene glycol and ammonia water are purchased from Chengdu Jinshan Chemical Reagent Co., Ltd., and all other chemicals used in the present invention are commercially available analytical grade commodities and are used directly without further purification. The deionized water used in all synthesis and treatment processes is prepared by the laboratory. In addition, it should be noted that the dosage of each reagent refers to weight parts, for example: 1 part can refer to 1g or 1kg or other mass measurement units, etc., and can be selected according to actual conditions (unless otherwise specified in the present invention, 1 part refers to 1g).

Claims

1. A bismuth-cerium bimetallic matrix composite material, characterized in that: The composite material includes Bi 19 Br3S 27 And the load on Bi 19 Br3S 27 CeO2 on.

2. The composite material according to claim 1, characterized in that: In the composite material, the loading amount of CeO2 is Bi 19 Br3S 27 5 to 35 wt% of the mass, preferably 10 to 30 wt%, more preferably 15 to 25 wt%, more preferably 17 to 22%.

3. A method for preparing a bismuth-cerium bimetallic matrix composite material or a method for preparing a bismuth-cerium bimetallic matrix composite material as claimed in claim 1 or 2, characterized in that: The method comprises the following steps: 1) The sulfur source, bismuth source and bromine source are subjected to liquid phase thermal synthesis reaction, and solid-liquid separation is performed to obtain Bi 19 Br3S 27 ; 2) Change Bi 19 Br3S 27 Add to the cerium source solution and mix evenly, then add alkali to the mixed system for mixing reaction. 19 Br3S 27 Bi loaded with CeO2 is precipitated on the surface 19 Br3S 27 , solid-liquid separation to obtain bismuth-cerium bimetallic matrix composite material.

4. The method according to claim 3, characterized in that: The sulfur source is elemental sulfur and / or an organic sulfur compound. Preferably, the organic sulfur compound includes but is not limited to one or more of thiols, thioethers, thiophenols, disulfides, polysulfides, and thiocarbonyl compounds. More preferably, the organic sulfur compound is one or more of thiourea, thioacetamide, and thioacetone.

5. The method according to claim 3 or 4, characterized in that: The bismuth source is one or more of bismuth nitrate, bismuth sulfate, bismuth chloride, bismuth bromide, and bismuth sulfide, preferably one or more of bismuth nitrate, bismuth bromide, and bismuth sulfide.

6. The method according to any one of claims 3 to 5, characterized in that: The bromine source is one or more of liquid bromine, bromine salts, and brominated hydrocarbons, preferably one or more of hexadecyl ammonium bromide, sodium bromide, potassium bromide, bismuth bromide, and ethylene dibromide.

7. The method according to any one of claims 3 to 6, characterized in that: The cerium source is one or more of cerium (III) nitrate, cerium (IV) nitrate, cerium (III) sulfate, cerium (IV) sulfate, cerium (III) chloride, cerium (IV) chloride, preferably cerium (III) nitrate and / or cerium (IV) sulfate; As a preferred method, the cerium source and Bi 19 Br3S 27 The addition mass ratio is 5 to 35:100, preferably 10 to 30:100, and more preferably 15 to 25:

100.

8. The method according to any one of claims 3 to 7, characterized in that: The base is aqueous ammonia; preferably, the amount of aqueous ammonia added is such that the pH of the reaction system is 8 to 11.5, preferably 9 to 11, and more preferably 9.5 to 10.

5.

9. The method according to any one of claims 3 to 8, characterized in that: Step 1) is specifically as follows: firstly, a sulfur source, a bismuth source, and a bromine source are prepared into solutions respectively, and then mixed or dissolved together to obtain a mixed solution; then, the mixed solution is placed in a sealed reactor and reacted at 120 to 160° C. (preferably 130 to 150° C.) for 1 to 24 hours (preferably 6 to 18 hours) to obtain a crude product; the crude product is washed with water and ethanol (for example, washed to neutrality); and finally dried (for example, vacuum dried at 60 to 80° C. for 1 to 12 hours) to obtain Bi 19 Br3S 27 ; and / or Step 2) is specifically: after the cerium source is made into a solution, Bi is added thereto. 19 Br3S 27 , after mixing evenly, add alkali and stir the reaction at 40-60°C (preferably 45-55°C) for 5-36h (preferably 8-30h) to obtain a crude product, then wash the crude product with water and ethanol (for example, wash to neutrality), and finally dry it (for example, dry it at 60-80°C for 1-12h) to obtain a bismuth-cerium bimetallic matrix composite material.

10. Use of a bismuth-cerium bimetallic matrix composite material or the bismuth-cerium bimetallic matrix composite material as claimed in claim 1 or 2 or the bismuth-cerium bimetallic matrix composite material prepared by the method according to any one of claims 3 to 9, characterized in that: The bismuth-cerium bimetallic composite material is used as a photocatalytic material, and preferably the bismuth-cerium bimetallic composite material is used for photocatalytic CO2 reduction.

Citation Information

Patent Citations

  • Preparation method of CeO2-TiO2 composite aerogel for photocatalytic reduction of CO2

    CN114054013A

  • Preparation method of Co / C-TiO2 composite material and application of Co / C-TiO2 composite material in CO2 photocatalytic reduction

    CN115254115A

Cited By

  • Bimetal carbon dioxide capture and methanation catalytic material as well as preparation method and application thereof

    CN121911504A